The Influence of Price Discount Framing and Price Perception on Impulsive Buying with Pay Later Payment System as a Moderating Variable in E-Commerce - Ulfatisa Cahyani; Akhmad Saufi (Dinasti International Journal of Digital Business Management, 2023)
E-commerce has become an increasingly popular phenomenon in the current digital era. With technological advancements and the internet, e-commerce has transformed the way consumers shop and do business. Through e-commerce platforms, consumers can easily purchase various products and services online without having to go to physical stores. This research aims to determine the influence of Price Discount Framing, Price Perception on Impulsive Buying with the pay later payment system as a moderating variable. The research method used is quantitative research with a causal approach and survey method using a questionnaire as the data collection instrument. The sample of this research is e-commerce users who have used the pay later payment system. The collected data will be analyzed using multiple linear regression analysis. The results of this research indicate that price discount framing has a positive influence on impulsive buying in e-commerce. This means that when consumers see a price discount, they are more likely to make impulsive purchases. Additionally, price perception also has a positive influence on impulsive buying. The lower the price perception held by consumers, the greater the likelihood of them making impulsive purchases. However, the pay later payment system does not moderate the relationship between price discount framing and impulsive buying, as well as between price perception and impulsive buying. This means that the use of the pay later payment system does not affect the influence of price discount framing and price perception on impulsive buying in e-commerce. This research provides important contributions in understanding the factors influencing impulsive buying behavior in e-commerce. The findings of this research can be used by e-commerce companies to develop more effective marketing strategies in attracting consumers and increasing sales